Endless Journey of Adenosine Signaling in Cardioprotective Mechanism of Conditioning Techniques: Clinical Evidence - Kumar, Kuldeep; Singh, Nirmal; Yadav, Harlokesh N.; Maslov, Leonid; Jaggi, Amteshwar Singh (Current Cardiology Reviews, 2023)
Myocardial ischemic injury is a primary cause of death among various cardiovascular disorders. The condition occurs due to an interrupted supply of blood and vital nutrients (necessary for normal cellular activities and viability) to the myocardium, eventually leading to damage. Restoration of blood supply to ischemic tissue is noted to cause even more lethal reperfusion injury. Various strategies, including some conditioning techniques, like preconditioning and postconditioning, have been developed to check the detrimental effects of reperfusion injury. Many endogenous substances have been proposed to act as initiators, mediators, and end effectors of these conditioning techniques. Substances, like adenosine, bradykinin, acetylcholine, angiotensin, norepinephrine, opioids, etc., have been reported to mediate cardioprotective activity. Among these agents, adenosine has been widely studied and suggested to have the most pronounced cardioprotective effects. The current review article highlights the role of adenosine signaling in the cardioprotective mechanism of conditioning techniques. The article also provides an insight into various clinical studies that substantiate the applicability of adenosine as a cardioprotective agent in myocardial reperfusion injury.
Keywords: preconditioning